Analysis of Genetic Diversity and Relationships of Local Walnut Populations in the Western Caspian Region of the North Caucasus - Ivan Suprun; Ilya Stepanov; Dzhalaludin Anatov (Horticulturae)
Common walnut (Juglans regia L.) is a valuable nut crop widely distributed within the temperate climate zone. It has several secondary centers of origin associated with refugia formed during the LGM (Last Glacial Maximum) period, one of which was presumably located in the Caucasus region. Currently, walnut populations of the Caucasus are studied fragmentarily, especially in the northeast. Our study is aimed at investigating the genetic diversity, population structure, and possible walnut introduction processes in the Caspian region of the Northeast Caucasus (Dagestan). Genotyping using 11 SSR markers was performed for 158 samples from local walnut populations. Also, to identify the introduction facts, 42 varieties of different geographical origin were added to research. The SSR markers genetic diversity in the analysis of population varied from four to 20 alleles per locus, with an average value of 9.82. Analysis of the genetic structure revealed significant genetic differences between the subpopulations of the Mountain and Flatland Dagestan. Presumably, the structure of the gene pool could have been influenced by terrain factors and ethnocultural characteristics. Subpopulations of Flatland Dagestan have an intermediate position between the western cultivars and the gene pool of Mountain Dagestan, which subpopulations showed significant genetic isolation. In the studied samples set of population selections, the established introduction facts were rare. We have suggested that a significant part of the walnut gene pool from Mountain Dagestan has an autochthonous origin from plants that survived the LGM in the Caucasian refugia. Our results are the basis for further studies of the local gene pool and verification of hypothesis about the presence of an indigenous germplasm preserved in this region from the LGM period.